Analisis Tingkat Kesehatan Bank Melalui Laporan Keuangan Periode 2017-2021 Dengan Menggunakan Metode Perhitungan CAMEL: Studi Pada Bank NTB Syariah - Nur Sa’idaturrohmah; Nurwinsyah Rohmaningtyas; Zamrotin Aulan Nisak (Program Studi Ekonomi Syariah Fakultas Ekonomi dan Bisnis Islam Institut Agama Islam Tarbiyatut Tholabah, 2023)
Banks are an important element of the state in improving people's living standards. Because with banks, people can collect and distribute money easily and efficiently. Therefore, the health of a bank needs to be considered so that its operational conditions can run in accordance with procedures. The purpose of this study is to analyze the health of NTB Syariah banks from the 2017-2021 financial statements. The method used in this study is quantitative descriptive using the CAMEL (Capital, Assets, Management, Equity, Liquidity) calculation method. The result of this study is that the condition of the NTB bank after calculation analysis has a very healthy condition in several ratios. But in addition to very healthy health conditions, there are also those who are in a healthy condition only, there are also those who enter the specifications of conditions that are quite healthy in several other calculation ratios. Therefore, it is hoped that this NTB bank can improve its operational activities to be even better in the future, so that it can also improve the level of health in the bank.